1998
DOI: 10.3171/jns.1998.89.1.0060
|View full text |Cite
|
Sign up to set email alerts
|

Dual-isotope single-photon emission computerized tomography scanning in patients with glioblastoma multiforme: association with patient survival and histopathological characteristics of tumor after high-dose radiotherapy

Abstract: Dual-isotope SPECT data correlate with histopathological findings made at reoperation and with survival in patients with malignant gliomas after surgical and high-dose radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…In contrast to PET, which remains a highly expensive diagnostic modality, SPECT is widely available and routinely used, even in less developed countries. In previous studies, higher tracer uptake by glioma on SPECT was shown to be associated with higher grade and decreased response to chemotherapy of gliomas (11)(12)(13)(14). In addition, higher technetium-99m-methoxyisobutylisonitrile ( 99m Tc-MIBI) uptake was demonstrated to correlate with higher proliferative potential of gliomas and with worse survival (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to PET, which remains a highly expensive diagnostic modality, SPECT is widely available and routinely used, even in less developed countries. In previous studies, higher tracer uptake by glioma on SPECT was shown to be associated with higher grade and decreased response to chemotherapy of gliomas (11)(12)(13)(14). In addition, higher technetium-99m-methoxyisobutylisonitrile ( 99m Tc-MIBI) uptake was demonstrated to correlate with higher proliferative potential of gliomas and with worse survival (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…That study also showed that the ADC ratios in the white matter tracts in the perilesional edema were significantly higher in patients with radiation injury compared with those with recurrent tumor and that the fractional anisotropy (FA) ratios were significantly higher in normal-appearing white matter tracts adjacent to the edema in patients diagnosed with radiation injury compared with those with recurrent tumors. 7 Thallium 201 ( 201 Tl) or 99mTc hexamethylpropyleneamine oxime single-photon emission tomography (HMPAO SPECT) or both [12][13][14] have been reported as useful techniques to discriminate tumor progression and radiation injury. It has been suggested that the combination of lowthallium and low-HMPAO uptake was associated with benign radiation change; whereas increased uptake of either agent or both was associated with recurrent/persistent tumor at biopsy and a poor prognosis.…”
mentioning
confidence: 99%
“…Recurrence was confirmed in 12 of their 13 patients, with 201 Tl tumor/scalp ratios of 3.5 or greater and with 99m Tc HMPAO tumor/cerebellum ratios of 0.51 or more. Schwartz et al 13 observed a similar relation, in terms of survival, using dual-isotope SPECT with 201 Tl and 99m Tc HMPAO. One-year survival was 6.7% if 201 Tl tumor/scalp ratios were 3.5 or greater and 99m Tc HMPAO tumor/cerebellum ratios were 0.51 or more, compared to 83% with 201 Tl tumor/scalp ratios of less than 2 and 99m Tc HMPAO tumor/cerebellum ratios less than 0.5.…”
Section: Discussionmentioning
confidence: 51%
“…[11][12][13][14][15][16] Most of these studies demonstrated the utility of 201 Tl-SPECT either alone or with dual-isotope SPECT with 99m Tc-hexamethylpropyleneamine oxime (HMPAO) in the follow-up evaluation of primary brain tumors. [13][14][15] A comparative assessment of 201 Tl-SPECT with CT was reported by Lorberboym et al 16 in high-grade gliomas following surgery, radiation, and/or chemotherapy during a mean follow-up period of 15 months. Because radiation-induced necrosis represents late radiation changes, studies with a longer duration of follow-up could further help to ascertain the predictive values of CT and 201 Tl-SPECT in post-irradiated brain tumors.…”
Section: Introductionmentioning
confidence: 99%